Intramolecular interactions between the SRC homology 3 and guanylate kinase domains of discs large regulate its function in asymmetric cell division. - Newman, R.A.; Prehoda, K.E. (Journal of Biological Chemistry, 2009)
Membrane-associated guanylate kinases (MAGUKs) regulate the formation and function of molecular assemblies at specialized regions of the membrane. Allosteric regulation of an intramolecular interaction between the Src homology 3 (SH3) and guanylate kinase (GK) domains of MAGUKs is thought to play a central role in regulating MAGUK function. Here we show that a mutant of the Drosophila MAGUK Discs large (Dlg), dlg(sw), encodes a form of Dlg that disrupts the intramolecular association while leaving the SH3 and GK domains intact, providing an excellent model system to assess the role of the SH3-GK intramolecular interaction in MAGUK function. Analysis of asymmetric cell division of maternal-zygotic dlg(sw) embryonic neuroblasts demonstrates that the intramolecular interaction is not required for Dlg localization but is necessary for cell fate determinant segregation to the basal cortex and mitotic spindle alignment with the cortical polarity axis. These defects ultimately result in improper patterning of the embryonic central nervous system. Furthermore, we demonstrate that the sw mutation of Dlg results in unregulated complex assembly as assessed by GukHolder association with the SH3-GK versus PDZ-SH3-GK modules of Dlg(sw). From these studies, we conclude that allosteric regulation of the SH3-GK intramolecular interaction is required for regulation of MAGUK function in asymmetric cell division, possibly through regulation of complex assembly.